Intelligent and active packaging for fruits and vegetables - Wilson, Charles L. (CRC Press, 2007)
Wilson brings together 17 chapters in a volume that describes the development and use of intelligent and active packaging, aiming to help bring fresh and safe produce to consumers. The history of these packaging methods is detailed, along with discussions of modified atmosphere packaging, lessons learned from fish and meat packaging, the interaction of food and packaging contents, natural nontoxic insect repellent materials, temperature monitoring, consumer needs, needs in developing countries, regulation, and other topics